2020
DOI: 10.3390/atmos11040332
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Trend Analysis of Precipitation in the Lake Issyk-Kul Basin, Kyrgyzstan

Abstract: The analysis of various characteristics and trends of precipitation is an essential task to improve the utilization of water resources. Lake Issyk-Kul basin is an upper alpine catchment, which is more susceptible to the effects of climate variability, and identifying rainfall variations has vital importance for water resource planning and management in the lake basin. The well-known approaches linear regression, Şen’s slope, Spearman’s rho, and Mann-Kendall trend tests are applied frequently to try to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 54 publications
3
58
0
1
Order By: Relevance
“…As reported by Alifujiang, Abuduwaili [74], the ITA method's application at three sites in the Issyk-Kul Basin revealed that the precipitation exhibited significant increasing trends in summer and winter. Moreover, utilization of the MK trend test and ITA method demonstrated that the percentage of time series with significant positive trends of monthly precipitation was decreased from north to south by Alifujiang.et.al [74]. This study revealed that in the summer and winter seasons, the data series of most hydrological stations fell above the 1:1 (45 • ) line.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…As reported by Alifujiang, Abuduwaili [74], the ITA method's application at three sites in the Issyk-Kul Basin revealed that the precipitation exhibited significant increasing trends in summer and winter. Moreover, utilization of the MK trend test and ITA method demonstrated that the percentage of time series with significant positive trends of monthly precipitation was decreased from north to south by Alifujiang.et.al [74]. This study revealed that in the summer and winter seasons, the data series of most hydrological stations fell above the 1:1 (45 • ) line.…”
Section: Discussionsupporting
confidence: 54%
“…River discharge is determined by rainfall, which falls in the catchment area, and by evaporation, which depends on air temperature [72,73]. As reported by Alifujiang, Abuduwaili [74], the ITA method's application at three sites in the Issyk-Kul Basin revealed that the precipitation exhibited significant increasing trends in summer and winter. Moreover, utilization of the MK trend test and ITA method demonstrated that the percentage of time series with significant positive trends of monthly precipitation was decreased from north to south by Alifujiang.et.al [74].…”
Section: Discussionmentioning
confidence: 81%
“…The comparative analysis of data series can be carried out without statistical assumptions [19] and the resulting graphs facilitate the statistical interpretation [38]. The method has been intensively used in the past decade to identify trends on extreme seasonal and annual value sets for climatic and hydrological parameters [39,40]. The ease of tracking trends by comparative analysis of data strings has led to the application of this method to identify solar radiation trends [41] and can be included in the analysis of trends of groundwater levels connected with different extreme hydroclimatic phenomena [42] or climatic changes [43].…”
Section: Resultsmentioning
confidence: 99%
“…Otherwise, the alternative hypothesis is the existence of a statistically significant decreasing/increasing trend in the given time series. Şen's innovative trend analysis methodology was commonly implemented to hydroclimatological time series observed at different locations through the world (Şen, 2014 and2015;Kişi et al, 2015;Ay et al, 2018;Gedefaw et al, 2018;Alifujiang et al, 2020).…”
Section: Innovative Trend Analysis Methodsmentioning
confidence: 99%